2019
DOI: 10.1021/acs.langmuir.9b02404
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Lipid Transfer in Microbubble-Mediated Drug Delivery

Abstract: Sonoporation, the permeabilization of cell membranes following exposure to microbubbles and ultrasound, has considerable potential for therapeutic delivery. To date, engineering of microbubbles for these applications has focused primarily upon optimizing microbubble size and stability, or attachment of targeting species and/or drug molecules. In this work, it is demonstrated that the microbubble coating can also be tailored to directly influence cell permeabilization. Specifically, lipid exchange mechanisms be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 55 publications
(90 reference statements)
2
18
0
Order By: Relevance
“…In the previous in vitro study, it was hypothesized that the observed increase in cell membrane permeability was due the incorporation of the lysolipid into the membrane and the corresponding reduction in the energy required for pore formation and/or increase in pore stability. [ 62 ] As mentioned in the introduction, it is possible that a similar mechanism is responsible for the increase in US‐BBBD, either through pore formation facilitating transcellular transport or tight junction disruption. It was, however, not possible to determine this from the histological work in this study and further investigation would be needed, e.g., in an in vitro BBB system.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the previous in vitro study, it was hypothesized that the observed increase in cell membrane permeability was due the incorporation of the lysolipid into the membrane and the corresponding reduction in the energy required for pore formation and/or increase in pore stability. [ 62 ] As mentioned in the introduction, it is possible that a similar mechanism is responsible for the increase in US‐BBBD, either through pore formation facilitating transcellular transport or tight junction disruption. It was, however, not possible to determine this from the histological work in this study and further investigation would be needed, e.g., in an in vitro BBB system.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…[ 62 ] These Lyso‐MBs have been shown to cause an approximately fivefold increase in the cellular uptake of a model drug in vitro compared to MBs containing no lysolipid (Control‐MBs). [ 62 ] Importantly, these Lyso‐MBs were also shown to be nontoxic in the absence of ultrasound. [ 62 ] The detailed mechanisms of US‐BBBD have yet to be conclusively established, but both transcellular transport and tight‐junction disruption have been proposed [ 59 ] and hence lysolipids might be expected to have a similar effect upon BBB permeability; by enabling either endothelial cell membrane poration or disruption of the lipid structures comprising tight junctions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations